2004
DOI: 10.1080/13102818.2004.10817142
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Exercise on the Immune Parameters and Stress Hormones in Elite Sportswomen

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
46
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(56 citation statements)
references
References 34 publications
10
46
0
Order By: Relevance
“…Cortisol degradation increases in obese individuals due to excess adipose tissue; the serum cortisol level is kept normal by the compensatory effects of adrenocorticotrophic hormone. 20,40 Anderson et al 40 found no significant relationship between minimal weight loss and nocturnal cortisol secretion. In the present study, LDL levels decreased and HDL levels increased after 12 weeks of exercise.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cortisol degradation increases in obese individuals due to excess adipose tissue; the serum cortisol level is kept normal by the compensatory effects of adrenocorticotrophic hormone. 20,40 Anderson et al 40 found no significant relationship between minimal weight loss and nocturnal cortisol secretion. In the present study, LDL levels decreased and HDL levels increased after 12 weeks of exercise.…”
Section: Discussionmentioning
confidence: 99%
“…37 Similar to the results obtained in experiments using animal models, both insulin and cortisol have been shown to be potent promoters of leptin production in cultured human adipocytes. 20,37,38 Insulin and, less remarkably, cortisol were found to have significant positive effects on serum leptin, whereas dehydroepiandrostenedione had a weaker negative influence in a multiple regression analysis using BMI as an index of degree of body fat. 39 These findings are in agreement with experimental data that demonstrate that both insulin and cortisol are stimulators of leptin expression in cultured human adipocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the mechanisms of these immunological changes with training or exercise are still unclear. Adrenocorticotropin hormone, cortisol, catecholamines, and other hormones are known to cause redistribution of lymphocytes and to have direct effects on lymphocyte function [12,19,21]. Several factors such as type, duration, intensity, and program of exercise have also important effects on immune response to exercise [20,28].…”
Section: Introductionmentioning
confidence: 98%
“…The immune system is a multifaceted array of cells, proteins, and compounds that respond sensitively to a variety of stimuli such as acute exercise and prolonged training in athletes [9][10][11][12][13][14][15][16][17][18][19][20][21][22]. In elite athletes, immunological alterations reduce performance and endurance levels [13,18,19] associated to decreased immune function and increased susceptibility to infections [9].…”
Section: Introductionmentioning
confidence: 99%